ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBENTUKAN RISK MANAGEMENT COMMITTEE Studi Empiris Perusahaan Non Finansial yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2011 - Ana Khusnun Safitri; Wahyu Meiranto (Diponegoro Journal of Accounting, 2013)
The aim of this research is to analyze the factors which influential the establishment of Risk Management Committee (RMC). There are two types of RMC, the one that combined with the audit committee and seperated from the audit committee. The factors that used in this research are board of director characteristic and firm characteristic that consist of proportion of independent commissioner, board size, board meeting, commissioner with accounting/finance expertise, and leverage, also firm size as control variabel.Sample of this research were 204 samples from non financial companies  listed in Indonesia Stock Exchange for the observation period of 2008 until 2011. Collecting data in this research used a purposive sampling method. This research used logistic regression to analyze data.The results of this research indicated that firm size affected positively and significant with the establishment of RMC that combined with audit committee and separated RMC. The other variables   (proportion independent commisioner, board size, board meeting, commisioner with accounting/financial expertise, leverage) have no significant association with the establishment of RMC that combined with audit committee and separated RMC.